A biblical theology of the Holy Spirit - Burke, Trevor J. 1956-; Warrington, Keith 1952- (London SPCK, 2014)
The Pentateuch /Walter C. Kaiser Jr. --The historical books /David Firth --The wisdom literature /Craig G. Bartholomew --Isaiah /Wonsuk Ma --Jeremiah /Andrew Davies --Ezekiel /James Robson --The Book of the Twelve /Martin Clay --The synoptic gospels /Keith Warrington --The gospel of John /Gary M. Burge --Acts /Matthias Wenk --Romans /Trevor J. Burke --1 Corinthians /William P. Atkinson --2 Corinthians /Moyer Hubbard --Galatians /James D.G. Dunn --Ephesians /Max Turner --1 Thessalonians /Volker Rabens --The pastoral epistles /Mathew Clark --Hebrews /Alan K. Hodson --1 and 2 Peter /Verena Schafroth --The Johannine epistles /John Christopher Thomas --Revelation /John Christopher Thomas.
Includes bibliographical references (pages 269-286) and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Holy Spirit -- Biblical teaching; Holy Spirit ; Biblical teaching; Heiliger Geist; Biblische Theologie